Characterization of the Humification Degree of Peat Soils under Cultivation of Sago and Oil Palm Plantations - Cecelyea, Jumin (Universiti Malaysia Sarawak (UNIMAS), 2019)
Sago palm (Metroxylon sagu) and oil palm (Elaeis guineensis) is a tropical crop that can adapt the acidic condition of peat soil, which is cultivated at large scale in Sarawak (Malaysia). The question is whether this large-scale development on peat soil are sustainable because of the challenges in their production yield. The production of sago palm and oil palm on deep peat are inconsistent, and not all the tree is able to grow to maturity and produce a yield. Besides, the production yield of the oil palm and sago palm at the mineral soil is greater than the one been cultivated on deep peat soil. For this reason, it is hypothesis that the extent of humification may have been the root cause to the slower and poorer performance of oil palm and sago palm on deep peat. This study is set out to investigate humification degree of peat soil under oil palm and sago palm plantations to provide a deeper insight. The soil samples were collected from the sago palm and oil palm estate. The physical and chemical soil characterisation were conducted between the sample’s origin and depth. Meanwhile, the carbon dioxide measurement was only conducted on the surface soil in oil palm estate and forest. The result indicated the peat soil in sago palm and oil palm had the most nutrient at the surface soil while, the degree of humification decreased with increasing depth. The trunk performance at trunking plot might be due to higher conductivity (460.00 µScm-1) (p<0.05) and lower C/N ratio (47.27%) (p> 0.05) compared to the non-trunking plot at the surface soil, while the FTIR shown the uncultivated peat was humified than cultivated peat because the latter was continuously replenished with new plant matter. On the basis of FTIR spectroscopy, no significant difference was found between cultivated peat sampled adjacent to trunking hand non-trunking palms. On the other hand, the UV-Vis and FTIR data suggested lower humification degree in the underlying peat which may have led to inconsistent growth. Meanwhile, the oil palm result shown the forest was more humified than the oil palm estate with significantly higher in conductivity (451.87 µScm-1) (p<0.05). The leaching of K (0.21-0.50 cmolc.kg-1) and Ca (0.55-1.119 cmolc.kg-1) (p<0.05) at the oil palm estate indicated the estate has lower nutrient, the lower C/N (21.43%) (p>0.05) in forest revealed a higher degree of humification, the higher N-enrich litter falls led to higher nitrogen fixation in the forest. Besides, the FTIR spectra suggested the forest is more humified than the oil palm estate and the forest is significantly has lower carbon dioxide flux (1.04 kg CO2 m-2 yr-1) than oil palm estate (1.16 kg CO2 m-2 yr-1). However, the Pearson correlation shown a weak liner regression between the degree of humification and carbon dioxide flux, R2=0.1516 in oil palm and R2= 0.0005 for forest. The correlation coefficient (r) for oil palm and forest is 0.389 and 0.023 (p>0.05). The carbon dioxide was not influence by the degree of humification nevertheless the higher air (27.2-33.3 °C) and soil temperature (27.0-28.4 °C) (p<0.05) at oil palm estate might be the factor for the higher carbon dioxide flux. Keywords: Decomposition, carbon dioxide flux, soil degradation, histosol, soil fertility, productivity yield, Sarawak.